HPLC method for novel cannabinoid separation with electrochemical detection on boron-doped diamond electrode - Belbasi, Zeynab; Petr, Jan; Hrbac, Jan; Jirovsky, David (Journal of pharmaceutical and biomedical analysis, 2025)
In this study, we developed a novel and environmentally friendly method for the determination of selected cannabinoids - cannabidiol, cannabinol, tetrahydrocannabinol, JWH 073 synthetic cannabinoid, hexahydrocannabinol (HHC), and hexahydrocannabinol-O-acetate - using high-performance liquid chromatography with electrochemical detection. The method employs a boron-doped diamond working electrode, which offers significant advantages in comparison with commonly used materials. Its main strengths include low background currents, reduced fouling, and an extended potential window, making it suitable for detecting compounds that are not readily oxidizable. The chromatographic system utilized a reversed-phase Gemini C18 column with a mobile phase consisting of acetonitrile and 25 mM phosphate buffer (pH 4.4) in step-gradient mode from 68 % to 88 % acetonitrile. The separation and determination of cannabinoids were optimized to be completed in less than 25 min. Hydrodynamic voltammetry was performed to identify the optimal potential for the amperometric detection, with a working potential of + 1400 mV (vs. Pd/H₂) providing the best analytical response based on S/N ratio. Under these optimal separation and detection conditions, the limits of detection were within the range of 6.1-666 nM (for cannabidiol and 9(R)-hexahydrocannabinol-O-acetate), while the response was linear within the concentration range measured up to 10 μM. The method demonstrated good linearity, precision, and sensitivity, with limits of detection and quantitation reaching nanomolar levels. The developed method was successfully applied to commercial samples of HHC jelly bears and HHC distillate.
Keywords: Electrochemical Techniques; HHC; diamant; HPLC; Cannabinoids; Boron; Reproducibility of Results; vysokoúčinná kapalinová chromatografie; CBD; kanabinoidy; Diamond; Electrochemical detection; reprodukovatelnost výsledků; limita detekce; Chromatography, High Pressure Liquid; Electrodes; Boron doped diamond; THC; elektrochemické techniky; Limit of Detection; elektrody; bor